Quality of life aspects in the management of thyroid cancer. Issue 6 (June 2015) - Duan, H.; Gamper, E.; Becherer, A.; Hoffmann, M.
Highlights We summarise the presentations and discussions from one session of a meeting entitled Thyroid cancer: nodule to cure – the controversies. Quality of life is becoming an increasingly important issue but is difficult to define and address. Patient perspectives on quality of life often differ from medical experts. For patients, quality of life and emotional burden is not directly related to the severity of the disease for patients. The conclusions drawn from the discussion have a considerable impact on the quality of life of patients with thyroid cancer.